Canopy management through crop forcing impacts grapevine cv. ‘Touriga Nacional’ performance, ripening and berry metabolomics profile - L. Cabral, Inês; Teixeira, António; Ferrier, Manon; Lanoue, Arnaud; Valente, Joana; Rogerson, Frank S.; Alves, Fernando; M. P. Carvalho, Susana; Gerós, Hernâni Varanda; Queiroz, Jorge (OENO one, 2023)
Climate changes are speeding up the maturation of grapes in numerous areas of the world, including in the Mediterranean basin, but warmer temperatures often uncouple technical and phenolic maturity, resulting in unbalanced wines. We tested the efficacy of crop forcing (CF) in delaying the maturation of cv. ‘Touriga Nacional’ vines of the Douro Region, and their impacts on plant performance, berry quality attributes and metabolome were also evaluated. In two consecutive seasons (2019 and 2020), CF was conducted 15 (CF1) and 30 (CF2) days after fruit set by hedging growing shoots to five nodes and removing summer laterals, leaves and clusters. Results showed that while CF2 delayed ripening up to 51 days till first autumn rainfall, which compromised optimal sugar ripeness, CF1 delayed the technical maturation by one month, but both treatments severely impacted the production, mainly CF1, which reduced grapevine yield up to 90 %. The effect of CF in protecting vines against drought stress was not evident, judging by the values of leaf pre-dawn water potential measured along both seasons. CF1 and CF2 resulted in berries with lower pH and higher titratable acidity than controls, while total phenolics content increased by up to 48 % in 2020. A UPLC–MS-based targeted metabolomic analysis showed that CF increased the relative abundance of key metabolites like flavan-3-ols (i.e., catechin gallate increased by up to 661 %), trihydroxylated anthocyanins (i.e., delphinidin-3-O-glucoside increased by up to 656 % after CF2) and stilbenes (resveratrol increased by up to 700 % after CF2) with potential positive impacts in wine quality.